2018
DOI: 10.3389/fmicb.2018.02059
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Probiotic Effect of Lactococcus lactis WFLU12 on Low-Molecular-Weight Metabolites and Growth of Olive Flounder (Paralichythys olivaceus)

Abstract: The use of probiotics is considered an attractive biocontrol method. It is effective in growth promotion in aquaculture. However, the mode of action of probiotics in fish in terms of growth promotion remains unclear. The objective of the present study was to investigate growth promotion effect of dietary administration of host-derived probiotics, Lactococcus lactis WFLU12, on olive flounder compared to control group fed with basal diet by analyzing their intestinal and serum metabolome using capillary electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 84 publications
0
28
0
Order By: Relevance
“…Previous studies have shown the importance of arginine and its derivatives, citrulline and ornithine, in the gastrointestinal tract of farmed fish 43 45 . Biosynthesis of arginine, citrulline and ornithine has previously been investigated in Mycoplasma , since this pathway is an important energy source in other Mycoplasma species 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the importance of arginine and its derivatives, citrulline and ornithine, in the gastrointestinal tract of farmed fish 43 45 . Biosynthesis of arginine, citrulline and ornithine has previously been investigated in Mycoplasma , since this pathway is an important energy source in other Mycoplasma species 22 .…”
Section: Discussionmentioning
confidence: 99%
“…While it is not considered a typical resident of the gastrointestinal tract, L. lactis is capable of surviving in the gut environment [ 71 , 72 ], where it may interact with the mucus layer [ 73 ]. This species has been used as a probiotic in red sea bream ( Pagrus major ), resulting in a higher final weight, percent weight gain, and specific growth rate [ 74 ], as well as in olive flounder ( Paralichythys olivaceus ), where it was found to increase levels of growth-promoting metabolites, such as short-chain fatty acids, citrulline, taurine and vitamins [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the importance of arginine and its derivatives citrulline and ornithine, in the gastrointestinal tract of farmed sh [41][42][43] . Biosynthesis of arginine, citrulline and ornithine have previously been investigated in Mycoplasma, since this pathway is an important energy source in other Mycoplasma species 22 .…”
Section: Discussionmentioning
confidence: 99%